Elastically isotropic truss-plate-hybrid hierarchical microlattices with enhanced modulus and strength - Wang, Yujia (2023)
Bioinspired hierarchical design principles have been employed to create advanced architected materials. Here, a new type of truss-plate-hybrid two-level hierarchical architecture is created, referred to as the ISO-COP hierarchical lattice (isotropic truss at the first level and cubic+octet plate at the second level), in which truss-based unit cells are arranged according to the topology of the plate-based unit cell. Finite element analyses reveal that the ISO-COP hierarchical lattice outperforms the best existing octet-truss hierarchical lattices based on fractal geometries in achieving elastic isotropy and enhanced moduli. According to the designed architecture, ISO-COP and several other comparison hierarchical microlattices are fabricated via projection microstereolithography. In situ compression tests demonstrate that the fabricated ISO-COP microlattices exhibit elastic isotropy and enhanced moduli, as predicted from finite element simulations, and superior strength compared with existing fractal octet-truss hierarchical lattices. Theoretical models are further developed to predict the dependence of modulus and failure modes on two design parameters of the hierarchical lattices, with results in good agreement with those from experiments. This study relates mechanical properties of ISO-COP hierarchical lattices to their architectures at each level of hierarchy and exemplifies a route to harnessing hierarchical design principles to create architected materials with desired mechanical properties.